First records of teleomorph of an invasive fungus Erysiphe macleayae (Erysiphales) in Ukraine - Heluta, V.P.; Kovalchuk, V.P.; Chumak, P.Ya. (Український ботанічний журнал, 2016)
It is reported that in 2015 an invasive powdery mildew fungus, Erysiphe macleayae (Erysiphales, Ascomycota), formerly known in Ukraine only in its anamorph stage, began to form mature fruiting bodies on Chelidonium majus and Macleaya microcarpa (Papaveraceae). Morphologically, they are almost identical to the chasmothecia of Slovak specimens. Ukrainian materials are also similar to E. macleayae samples described from China although having slightly larger chasmothecia and slightly smaller asci and ascospores. Teleomorph of the fungus was found in three localities in the city of Kiev and Kiev Region. Another species of Macleaya, M. cordata, was infected only by the anamorph of E. macleayae. The specimens studied are stored in the National Herbarium of M.G. Kholodny Institute of Botany, National Academy of Sciences of Ukraine (KW). The authors assume that formation of fruiting bodies of E. macleayae may be caused by an extremely hot summer in 2015. Another possible explanation is that a new biotype of E. macleayae has migrated from South Asia into Ukraine and subsequently formed mature chasmothecia through the sexual process with the indigenous European populations of the fungus.